OEE(Overall Equipment Effectiveness) aplicado no suporte à decisão na aquisição de ativos de produção: um estudo de caso em uma indústria de autopeças - Oliveira, Luiz Antonio Fernandes de (2014)
Due to the high cost of money, although there are financing programs for the purchase of machinery and equipment, it is important to have in hand, reliable data to a proper decision, about where to invest these resources. It is because the assets value has a significant impact on costs. Thus to buy machine is a very important decision to be made without reliable data. This study aimed to present the indicator OEE (Overall Equipment Effectiveness) as a tool to aid the decision in this process. This indicator is aid to manager to know what the percentage of effective utilization of equipments. The methodology proposed in this work intended and assist in accurate measurement of OEE, show how it can be measured instantaneously, directly by operators , enabling a quickly reaction from the managers to avoid drifts from the OEE objective set when the equipment was purchased. This work is not intended to cover the acquisition of machinery and equipment, when they are intended for the exchange of obsolete equipment, or to meeting engineering specifications for which the existing facilities are not able to attend. That study examined an equipment that had an OEE of 62% with load of 3,146 machine hours, with availability of 3,996 hours. Future demand showed the need for 5272 hours of machine load. The study showed by simulations with numerical methods using response surfaces in which it was possible to increase the OEE to 82% and increase the working time available for 5285 hours, with the losses reduction by 30%, thus enabling delay buying new equipment for at least a year.